Hubungan Ketahanan Pangan Keluarga dengan Status Gizi Balita di Kecamatan Selo, Boyolali - Resthu Kirana; Luluk Lia Rakhma; Pramudya Kurnia (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
Household food security serves as a fundamental determinant of child nutritional outcomes, with under-five children being particularly susceptible to growth impairment due to inadequate dietary intake. This cross-sectional study investigated the association between household food security and the nutritional status of children residing in Selo Subdistrict, Boyolali Regency, an upland agrarian area with horticultural production dominance classified under disaster-risk zone (KRB III). A total of 108 households were recruited through proportional random sampling. Food security was evaluated using the Household Food Insecurity Access Scale (HFIAS), while nutritional status was assessed based on height-for-age z-scores (HAZ) according to WHO and Indonesian Miniktry of Health standards. Chi-square analysis was applied for bivariate testing. Findings revealed that 51.9% of participating households were food insecure and 48.1% of children exhibited stunted growth. A statistically significant relationship was identified between household food security status and stunting incidence (p = 0.002; OR = 3.431; 95% CI: 1.553–7.581), indicating a substantially elevated stunting risk among children from food-insecure households compared to their food-secure counterparts. These findings underscore that food insecurity in mountainous agricultural settings is not solely a matter of food availability, but critically involves constrained access to high-quality, diverse foods—particularly animal-sourced proteins. Consequently, efforts to address stunting must prioritize improvements in dietary quality and variety.